Development Of Ecotourism Through Tourist Village Marketing Strategies To Increase The Visit Of Tourists In Kapuas Hulu Regency - Utin Nina Hermina (Institute of Computer Science (IOCS), 2022)
The development of ecotourism in Kapuas Hulu regency have a couple of problems such as environment from natural resources that will soon become a tourist attraction, supporting infrastructures for the development of tourism in countryside, the lack of promotion from the government, lack of facility and service for tourists. Malemba tourist village is one of the tourist village that located in Kapuas Hulu regency, in the village there is a long house which is also used as homestay for tourist accommodation. But the unavailability to communicate due to language barrier, they commonly can’t be the tour guide for international nor the local tourists. The purpose of this study are to find marketing strategies through mix marketing (product, promotion, and price) that affect the increase of tourist village’s tourists in Kapuas hulu regency. The result of this study shows that tourism product from Malemba tourist village has already took tourist’s interest especially the natural tourism, but the price for it is quite pricy, specifically for transportation to the village itself could have an unstable price depending on nature’s condition and incoming tourist, the promotion is also still lacking, only a few promotion are done by the local communities and the government of tourism. The need of support particularly from the government of tourism to help promote and fix the facilities and infrastructure so that the price of the tourism attraction could be more affordable.